METAFORA DALAM PUISI KARYA CHAIRIL ANWAR - Heni Subagiharti; Diah Syahfitri Handayani; Murni Adawiyah (Smart Education, 2025)
Abstract: This study analyzes the metaphors in Chairil Anwar's poetry, which aims to (1) find out what metaphors are contained in Chairil Anwar's poetry. (2) To find out the metaphors in the poetry by Chairil Anwar. (3) To find out the reason the author uses the metaphor in his poem. The method used in this research is descriptive analysis method. Descriptive analysis is used to get a careful description of the contents of the poem. The results of this study show that the metaphor contained in Chairil Anwar's poetry describes how deep human